Mortality and readmission differences associated with after‐hours hospital admission: A population‐based cohort study in Queensland Australia. Issue 3 (27th March 2023) - Bell, Anthony; Boyle, Justin; Rolls, David; Khanna, Sankalp; Good, Norm; Xie, Yang; Romeo, Michele
Abstract: Background and Aims: Policy makers and health system managers are seeking evidence on the risks involved for patients associated with after‐hours care. This study of approximately 1 million patients who were admitted to the 25 largest public hospitals in Queensland Australia sought to quantify mortality and readmission differences associated with after‐hours hospital admission. Methods: Logistic regression was used to assess whether there were any differences in mortality and readmissions based on the time inpatients were admitted to hospital (after‐hours versus within hours). Patient and staffing data, including the variation in physician and nursing staff numbers and seniority were included as explicit predictors within patient outcome models. Results: After adjusting for case‐mix confounding, statistically significant higher mortality was observed for patients admitted on weekends via the hospital's emergency department compared to within hours. This finding of elevated mortality risk after‐hours held true in sensitivity analyses which explored broader definitions of after‐hours care: an "Extended" definition comprising a weekend extending into Friday night and early Monday morning; and a "Twilight" definition comprising weekends and weeknights. There were no significant differences in 30‐day readmissions for emergency or elective patients admitted after‐hours. Increased mortality risks for elective patients was found to be an evening/weekend effect rather than a day‐of‐week effect. Workforce metrics that played a role in observed outcome differences within hours/after‐hours were more a time of day rather than day of week effect, i.e. staffing impacts differ more between day and night than the weekday versus weekend. Conclusion: Patients admitted after‐hours have significantly higher mortality than patients admitted within hours. This study confirms an association between mortality differences and the time patients were admitted to hospital, and identifies characteristics of patients and staffing that affect those outcomes.